THE USE OF COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH THROUGH ENGLISH VILLAGE FOR IMPROVING AN TRANSACTIONAL LANGUAGE FUNCTION OF SPEAKING SKILL - Hengki Hengki; Ratna Ratna (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The objectives of this study are to investigate the effectiveness of CLT approach in interpersonal function of speaking and to investigate the effectiveness of CLT approach in transactional function of speaking. It was an experimental study by using one-group pretest-posttest design. The target population of this study was students of English department at the Islamic University of Kalimantan Indonesia Determining one class as research sample. The achievements of the students were further compared in terms of pre-test and post-test using the dependent t-test, the study found that students who are taught with CLT approach through English Community have better score on the post-test than on the pre-test for transactional function of speaking, it found the t-test is 9.417 with critical view of t at p > 001 of one tailed test is 3.307 (df =34). It means that there is a very significant impact on students’ skill in transactional function of speaking after following English community using CLT approach.